246 reasons to cheat: An analysis of students' reasons for seeking to outsource academic work. (June 2019) - Amigud, Alexander; Lancaster, Thomas
Abstract: This study examines the reasons students give for seeking unacceptable levels of help with completion of their academic work. It aims to fill the gap in the literature by presenting a comprehensive review of the first-person reasons students have given for requesting that someone else completes their assignments and assessments for them. To this end, we analyzed a dataset composed of 5, 000 messages from ten contract cheating services posted on the social media service Twitter. Unlike survey research that relies on participants' ability to recall and explain the events, this study uses discourse analysis that provides a snapshot of student behaviors from the moment they announce their intent to outsource the work, an area that has not previously been analyzed in the contract cheating research base. The reasons accompanying the solicitation of contract work were classified into five categories that include: academic aptitude, perseverance, personal issues, competing objectives, and self-discipline. One important insight of this study is that students appear to have a subjective threshold; they are willing to invest a certain amount of energy in any given assignment, and once the limit is reached outsourcing is sought as the means to quit without losing the qualification. Recommendations for addressing the issue of contract cheating and directions for future research are discussed. Highlights: Contract cheating services are actively using bots to engage with students on social media and market academic integrity breaching solutions to them. This study analyzes the first-hand accounts of students using social media to seek to outsource their academic assessments. Using social media, it is possible to identify the moment students give up on playing by the rules and plan to engage in cheating behavior. Outsourcing represents a behavior where students show they are quitting learning but do not wish to lose the qualification they were working towards. The factors influencing contract cheating are: academic aptitude, perseverance, personal issues, competing objectives, and self-discipline.